Sustainability and educational practice: a perspective from Japan - Carter, Peter (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3652, 2025)
This paper considers issues of sustainability in Japanese tertiary education from two viewpoints, namely whether the current high number of institutions relative to the declining youth population is likely to remain unchanged, and how Japanese universities do or do not engage in educational efforts to teach and research sustainability as a field. As such, the paper brings together two meanings of sustainability – that is, the sense of continuation, and that of furnishing a means of support – and then shows how, in the Japanese case, they are somewhat related due to historical, cultural, and religious reasons. With regard to the question of all current universities remaining open into the future, the available data is not particularly positive, and this may be especially true for privately-run institutions founded with religious principles at heart. As for teaching and researching sustainability, the picture is rather better, especially at public universities or at private universities willing to form partnerships with external organizations with relevant expertise. The paper concludes by describing a modestly successful program that might act as an exemplar for institutions seeking to create new sustainability-related programs for their own students. The Global Leadership Program collaborates with the local UN-Habitat Office, and sends its students to various domestic and international locations to work on sustainability issues.